Una lauda per Maria Maddalena nell’inedito laudario di tradizione ligure-piemontese di Agostino Perrone, frate in Provenza (ms. Béziers, CIRDÒC - Mediatèca occitana, 913. - Savio, Michela Del (Scripta, 2022)
MS Béziers, CIRDÒC - Mediatèca occitana, 913, which has never been studied until now (but in Brunel 1935, no. 250), is the focus of this contribution. The MS contains, in addition to prayers in Provençal, Latin and French, a small laudary of Ligurian-Piedmontese tradition: the collection hands down texts that also appear in many of the already known laudaries of north-western Italy, with very strong similarities to the ones from Finale Ligure (Orlando 1984 and Meliga 1992). A lauda for Mary Magdalene will be an opportunity to observe the belonging of the text to the mentioned tradition.